If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2y + 1) + 7(4y + 2) = 0 Reorder the terms: 5(1 + 2y) + 7(4y + 2) = 0 (1 * 5 + 2y * 5) + 7(4y + 2) = 0 (5 + 10y) + 7(4y + 2) = 0 Reorder the terms: 5 + 10y + 7(2 + 4y) = 0 5 + 10y + (2 * 7 + 4y * 7) = 0 5 + 10y + (14 + 28y) = 0 Reorder the terms: 5 + 14 + 10y + 28y = 0 Combine like terms: 5 + 14 = 19 19 + 10y + 28y = 0 Combine like terms: 10y + 28y = 38y 19 + 38y = 0 Solving 19 + 38y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-19' to each side of the equation. 19 + -19 + 38y = 0 + -19 Combine like terms: 19 + -19 = 0 0 + 38y = 0 + -19 38y = 0 + -19 Combine like terms: 0 + -19 = -19 38y = -19 Divide each side by '38'. y = -0.5 Simplifying y = -0.5
| 5sinx+12cosx-13=y | | m^3+8m-1=0 | | -50x^2+13=42x-39 | | 5+7y=2x+6+6y | | 4(8-5y)+2y=-40 | | 1(5x)-3=1 | | 7×3/4= | | 7×3/4 | | y-(4y-2)=14 | | 9y+2=7y+8 | | 4x^2-1400=0 | | 2x-7=5-x | | y=5ln*x/x-3 | | 27x=8 | | 4=x^2/3600-50x | | (2x+3y)dx=(5y-7x)dy | | 9x^3=1 | | x-9=2+8 | | (6x-x^2/100)-(2x) | | 3x+2=7x-50 | | x^2-6xy+y^2=C | | x+0.05x=13200 | | -12x+8=20 | | (x+2)(x+3)=(x+3)(x+2) | | y=2x^3-9x^2+12x-9 | | x-1/3x=26 | | 8x+2x=200-120 | | 0.111x+2y=1.6 | | you=-5x-1 | | 3(6+r)= | | 4x-(2x+6)=2(11-x) | | 12y+8(y+14)=178 |